A functional m6A‐RNA methylation pathway in the oyster Crassostrea gigas assumes epitranscriptomic regulation of lophotrochozoan development. (1st September 2020) - Le Franc, Lorane; Bernay, Benoit; Petton, Bruno; Since, Marc; Favrel, Pascal; Rivière, Guillaume
Abstract : N 6 ‐methyladenosine (m 6 A) is a prevalent epitranscriptomic mark in eukaryotic RNA, with crucial roles for mammalian and ecdysozoan development. Indeed, m 6 A‐RNA and the related protein machinery are important for splicing, translation, maternal‐to‐zygotic transition and cell differentiation. However, to date, the presence of an m 6 A‐RNA pathway remains unknown in more distant animals, questioning the evolution and significance of the epitranscriptomic regulation. Therefore, we investigated the m 6 A‐RNA pathway in the oyster Crassostrea gigas, a lophotrochozoan model whose development was demonstrated under strong epigenetic influence. Using mass spectrometry and dot blot assays, we demonstrated that m 6 A‐RNA is actually present in the oyster and displays variations throughout early oyster development, with the lowest levels at the end of cleavage. In parallel, by in silico analyses, we were able to characterize at the molecular level a complete and conserved putative m 6 A machinery. The expression levels of the identified putative m 6 A writers, erasers and readers were strongly regulated across oyster development. Finally, RNA pull‐down coupled to LC‐MS/MS allowed us to prove the actual presence of readers able to bind m 6 A‐RNA and exhibiting specific developmental patterns. Altogether, our results demonstrate the conservation of a complete m 6 A‐RNA pathway in the oyster and strongly suggest its implication in early developmental processes including MZT. This first demonstration and characterization of an epitranscriptomic regulation in a lophotrochozoan model, potentially involved in the embryogenesis, bring new insights into our understanding of developmental epigenetic processes and their evolution. Abstract : N 6 methylation of RNA (m 6 A‐RNA) is present in the oyster, differentially affects distinct RNA populations and displays variations across development associated with the regulation of putative m6A writers, eraser and readers. Readers bind m6A‐RNA in vitro and exhibit specific development stages, cell compartmentalization, expression profiles and functional annotation. We demonstrate the conservation of a complete m 6 A‐RNA pathway in a lophotrochozoan and strongly suggest its implication in early developmental processes including MZT.